Exploring the adoption of Lean principles in medical laboratory industry: Empirical evidences from Namibia. Issue 1 (5th March 2018) - Isack, Hilma Dhiginina; Mutingi, Michael; Kandjeke, Hileni; Vashishth, Abhishek; Chakraborty, Ayon
Abstract : Purpose: As the demand for efficiency and quality in the health-care industry has increased over the past few years, adoption of Lean principles and tools in the medical laboratory industry has become increasingly crucial. The purpose of this study is to explore the level of adoption, barriers and enablers of Lean principles and tools in the Namibian medical laboratory industry. Design/methodology/approach: A descriptive cross-sectional study was carried out to examine the level of usage, barriers and enablers, impact of Lean tools and to suggest appropriate strategies for adopting Lean in the Namibian medical laboratory services. Findings: Research findings reveal that Lean tools are moderately implemented in most laboratories. Standard operating procedures, root cause analysis, overall equipment effectiveness and visual management are the important Lean tools used in the industry. Results of the survey also show that Lean tools had a positive impact on operational performance, employee motivation, turnaround time and cost reduction. Furthermore, top management involvement, adequate training and proper planning emerged as important enablers, while lack of support from the management, financial constraint and staff resistant to change are major barriers to the adoption of Lean principles in the Namibian medical laboratory industry. Research limitations/implications: The paper has inherent limitations of survey research, which the authors will overcome by using case studies with medical laboratories. Practical implications: The findings of the authors' work will help in widening the application of Lean principles in more medical laboratories in Namibia and in other parts of the world. Originality/value: The paper is based on numerous health-care studies on Lean. This is one of the few papers investigating the adoption of Lean principles, specifically in medical laboratories, from an emerging economy such as Namibia.